Social Model of Disability: A Small-Scale Survey of the Bangladeshi Community in the London Borough of Tower Hamlets - Parveen, Syeda Sultana (Advances in Social Sciences Research Journal, 2021)
This study employs a small-scale survey to investigate the lives of Bangladeshi disabled residents in the London Borough of Tower Hamlets. Survey instruments include individual interviews and focus group discussions with people with disabilities in the Bangladeshi community. The paper also investigates the health and social care activities of Tower Hamlets Council through the lens of the social model of disability. The findings show that there are numerous facilities available for people with disabilities, but there is still a lack of satisfaction with the services provided to the community.